Bruchus rufimanus Boheman (Coleoptera: Bruchidae) في نمو وتطور خنفساء الباقلاء الكبير Match تأثير مثبط تصنيع الكايتين - شفيق, معـن عبد العزيز (Al-Nahrain Journal of Science, 2018)
Match, a benzoylphenylurea derivative, was tested topically at four doses (0.5, 1.0, 1.5 and 2.0 μg/insect) on adults of Bruchus rufimanus (Coleoptera: Bruchidae) (